Assessment of Cytokine and Chemokine Signatures as Potential Biomarkers of Childhood Community-acquired Pneumonia Severity: A Nested Cohort Study in India. Issue 1 (January 2017) - Saghafian-Hedengren, Shanie; Mathew, Joseph L.; Hagel, Eva; Singhi, Sunit; Ray, Pallab; Ygberg, Sofia; Nilsson, Anna
Abstract : Background: Pediatric community-acquired pneumonia (CAP) is a leading cause of childhood mortality in developing countries. In resource-poor settings, pneumonia diagnosis is commonly made clinically, based on World Health Organization guidelines, where breathing difficulty or cough and age-adjusted tachypnea suffice to establish diagnosis. Also, the severity of CAP is generally based on clinical features and existing biomarkers do not reliably correlate to either clinical severity or outcome. Here, we asked whether systemic immune and inflammatory mediators could act as biomarkers predicting CAP severity or outcome. Methods: Serum from a subset of a CAP cohort (n = 196), enrolled in India, classified according to World Health Organization criteria as having pneumonia or severe pneumonia, was used for simultaneous measurement of 21 systemic cytokines and chemokines. Results: We found significantly higher IL-6, IL-8, IL-13, IFN-γ and lower CCL22 concentrations in patients with severe compared with mild CAP ( P values: 0.019, 0.036, 0.006, 0.016 and 0.003, respectively). Based on higher MIP-1α, IL-8, IL-17 or lower CCL22 response pattern at the time of enrolment, children with fatal outcome showed markedly different pattern of inflammatory response compared with children classified with the same disease severity, but with nonfatal outcome ( P values: 0.043, 0.017, 0.008 and 0.020, respectively). Conclusions: Our results suggest a relation between an elevated mixed cytokine response and CAP severity on one hand, and a bias toward uncontrolled neutrophilic inflammation in subjects with fatal outcome on the other. Collectively our findings contribute to increased knowledge on new biomarkers that can potentially predict severity and outcome of childhood CAP in the future. Abstract : Supplemental Digital Content is available in the text.